An eco-friendly way to valorize winery wastewater and sewage sludge: Anaerobic co-digestion. (November 2020) - Zahedi, S.; Solera, R.; Pérez, M.
Abstract: Anaerobic digestion (AD) of sewage sludge (SS) and anaerobic co-digestion (AcoD) of SS and wine distillery wastewater (WDW) was investigated at different hydraulic retention times (HRTs), ranging from 20 to 8 d. The mixture of SS and WDW resulted in a highly improved quality of feedstock: soluble organic matter and organic matter easily accessible for acidification increased substantially (>60%), while non-solubilized organic matter decreased (>160%). AcoD of SS:WDW consequently yields higher values of average organic matter removals (48–66%) compared to AD of SS alone (42–58%), in keeping with the increase in specific methane productivity (SMP) (around 45%). Increasing the organic loading rate (OLR) or decreasing the HRT resulted in an increase in methane production (MP) and a decrease in SMP. Maximum values of MP in AD and AcoD were respectively 0.9 ± 0.2 L CH4 d −1 at an OLR of 8.2 and 5.4 kg TCOD m −3 d, corresponding to an HRT of 8 d. SMP values in AD and AcoD fell within the 200–300 L CH4 kg VS −1 and 300–400 L CH4 kg VS −1 range, respectively. This paper presents a low-cost strategy for wine producing countries to increase energy generation at wastewater treatment plants, as well as providing them with an interesting source of income. Highlights: Anaerobic co-digestion of sludge and wine distillery wastewater (AcoD of SS:WDW) is evaluated. WDW supposes an important contribution of easily accessible organic matter. WDW increase the specific methane production. AcoD of SS:WDW could be a sustainable strategy in wine producing countries. AcoD of the SS:WDW could mean an economic profit higher than 125 € d −1 .